1996
DOI: 10.1007/bf00186689
|View full text |Cite
|
Sign up to set email alerts
|

Axial structures control laterality in the distribution pattern of endothelial cells

Abstract: In the midline of the embryo an invisible barrier exists that keeps endothelial cells from migrating to the contralateral side. Interspecific grafting experiments between chick and quail were carried out in order to investigate the role of the axial structures in maintaining this barrier. The quail endothelial cells of the graft were therefore stained with QH1 antibody. In all experimental series quail paraxial mesoderm was used as a source of endothelial cells. First, a quail somite was transplanted either ip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 77 publications
(69 reference statements)
4
22
0
Order By: Relevance
“…What is the source of angioblasts that colonize the PNVP? We and others have shown that somite-derived angioblasts reproducibly contribute to PNVP formation (Wilting et al, 1995;Klessinger and Christ, 1996;Pardanaud et al, 1996;Pardanaud and Dieterlen-Lievre, 1999;Ambler et al, 2001), and in this study the neural tube was sufficient for formation of a somite-derived vascular plexus in collagen co-cultures. Presomitic mesoderm grafts placed next to a 'buffer' of avian cells that prevented direct contact with neural tube contributed to the PNVP, showing that progenitor/endothelial cells can migrate over a distance in response to neural tube vascular patterning signal(s).…”
Section: The Neural Tube As a Vascular Signaling Centersupporting
confidence: 66%
See 1 more Smart Citation
“…What is the source of angioblasts that colonize the PNVP? We and others have shown that somite-derived angioblasts reproducibly contribute to PNVP formation (Wilting et al, 1995;Klessinger and Christ, 1996;Pardanaud et al, 1996;Pardanaud and Dieterlen-Lievre, 1999;Ambler et al, 2001), and in this study the neural tube was sufficient for formation of a somite-derived vascular plexus in collagen co-cultures. Presomitic mesoderm grafts placed next to a 'buffer' of avian cells that prevented direct contact with neural tube contributed to the PNVP, showing that progenitor/endothelial cells can migrate over a distance in response to neural tube vascular patterning signal(s).…”
Section: The Neural Tube As a Vascular Signaling Centersupporting
confidence: 66%
“…Although the invasion of angiogenic sprouts into neural tissue has been described, the developmental processes that pattern the PNVP have not been investigated. Both quailchick and mouse-quail chimera analysis identified somitederived precursor cells as an important source of endothelial cells that comprise the PNVP (Wilting et al, 1995;Klessinger and Christ, 1996;Pardanaud et al, 1996;Pardanaud and Dieterlen-Lievre, 1999;Ambler et al, 2001). Moreover, our recent analysis of ES cell-derived grafts showed that VEGF signaling is involved in vascular patterning around the midline of higher vertebrates (Ambler et al, 2003).…”
Section: Introductionmentioning
confidence: 96%
“…In addition, chimera studies have confirmed the migratory potential of PECs. In a number of avian experiments, quailderived graft cells were found to disperse as far as 400 µm (Klessinger and Christ, 1996), in cranial, caudal, lateral and medial directions within their host environment (Noden, 1989;Noden, 1990;Pardanaud and Dieterlen-Lievre, 1999;Poole and Coffin, 1989;Wilting et al, 1995;Wilting and Christ, 1996). Similar results were obtained with mouse-quail chimeras (Ambler et al, 2001).…”
Section: Discussionmentioning
confidence: 61%
“…QH1 + ECs never crossed the dorsal midline (cf. Klessinger and Christ, 1996;Pardanaud et al, 1996). This aorta-associated QH1 pattern persisted until aortic hematopoiesis initiated, i.e.…”
Section: Unilateral Graftsmentioning
confidence: 99%